NILAI-NILAI PLURALISME DALAM AJARAN SOSIAL ISLAM; PERSPEKTIF FIKIH REALITAS - Jonwari Jonwari (LP2M Universitas Ibrahimy, 2013)
The history facts have shown that the Islamic law always paid attention at the reality of society in developing its legal pattern of istinbath. This is understandable because the placement of the fiqh (law) findings, in the context of reality, is another form of the application of ethical values which are highly recommended in Islam. Indeed the fiqh (law) resulted from istinbat can be integrated into ethical values so as to reflect the harmony in the community. Therefore, the observation on reality is a very necessary thing in order to formulate jurisprudence (law) with its correct and effective mechanism of istidlal. Then, the diversity of fiqh (law) formulations, at least, due to two things, namely: the problem of meaning limitations and problems in the application area of reality. Thus fiqh (law) became abundant and was reflected in the multi-volume books. It was because of its intensity related to reality. Statement that reality must be subject to fiqh (law) or the opposite is not the right thing. Fiqh (law) and the reality in the history of the Muslim community interact, influence, equip, and fill each other.